2009
DOI: 10.1016/j.ecl.2009.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Obesity: Etiology and Treatment

Abstract: Synopsis This paper reviews factors that contribute to excessive weight gain in children and outlines current knowledge regarding approaches for treating pediatric obesity. Virtually all of the known genetic causes of obesity primarily increase energy intake. Genes regulating the leptin signaling pathway are particularly important for human energy homeostasis. Obesity is a chronic disorder that requires long-term strategies for management. The foundation for all treatments for pediatric obesity remains restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 158 publications
(142 reference statements)
0
65
0
6
Order By: Relevance
“…32 Documenting the prevalence of engagement in high-risk behaviors for this already vulnerable subpopulation of adolescents is not only timely but also imperative, especially given health care providers' conundrum of how best to intervene when such youth are under their care. 33,34 Unfortunately, the weight loss intervention literature (eg, behavioral [35][36][37] and pharmacotherapy 38,39 ) has not progressed sufficiently, and thus, the vast majority of today's youth with extreme obesity will carry their excess weight and associated medical and psychosocial burden into adulthood. 12 In addition, as bariatric surgery emerges as a potential and viable treatment option for this age and weight status group [40][41][42] it is critical to establish a most comprehensive picture of the health and mental health needs of this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…32 Documenting the prevalence of engagement in high-risk behaviors for this already vulnerable subpopulation of adolescents is not only timely but also imperative, especially given health care providers' conundrum of how best to intervene when such youth are under their care. 33,34 Unfortunately, the weight loss intervention literature (eg, behavioral [35][36][37] and pharmacotherapy 38,39 ) has not progressed sufficiently, and thus, the vast majority of today's youth with extreme obesity will carry their excess weight and associated medical and psychosocial burden into adulthood. 12 In addition, as bariatric surgery emerges as a potential and viable treatment option for this age and weight status group [40][41][42] it is critical to establish a most comprehensive picture of the health and mental health needs of this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, it is unquestionable that the increase in fat storage is due to positive energy balance, situation where energy intake overcomes expenditure, part of the surplus energy being deposited. To explain why this phenomenon has been occurring in such a striking way for the past few years, many explanations may be brought forward but, generally speaking, all of them fit in three possibilities: 16 • Energy intake increased.…”
Section: Methodsmentioning
confidence: 99%
“…27 In fact, studies of association in the whole genome have demonstrated a variety of genetic loci associated to the most common form of obesity, and more than 300 genetic loci potentially involved with obesity have been identified in human beings as well as in animals. 16 Polymorphisms in the FTO gene, for instance, are associated to human obesity, leading to an increase in food intake and the preference for high energy food. 28 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…La obesidad, según Crocker & Yanovski (2009), es una enfermedad crónica de origen multifactorial, producida por un balance energético positivo mantenido en el tiempo, traduciéndose posteriormente en una acumulación excesiva de peso y masa grasa corporal, lo cual es perjudicial para la salud. El exceso de grasa en los niños se relaciona con riesgo cardiovascular y diabetes tipo 2 en la edad adulta, un buen método antropométrico para medir la adiposidad central es la relación cintura-estatura, cuando esta relación es ≥0,50, identifica a población de riesgo (Arnaiz et al, 2014).…”
Section: Introductionunclassified